Effective leadership practices of Muslim women academic leaders - Almaki, Samah Hatem; Silong, Abu Daud; Idris, Khairuddin; Abd. Wahat, Nor Wahiza (Medwell Journals, 2016)
Newer research on women in leadership indicated a growing trend of woman to assume leadership position worldwide and the substantial progress achieved by women in assuming and holding a leadership role. This study explores the leadership practices of Muslim women academic leaders by using a qualitative approach. The study outlined in this study investigates these phenomenons through using in-depth-interviews to identify leadership practices. Participants are Muslim women academic leaders in University Putra Malaysia in Malaysia and King Abdul Aziz University in Saudi Arabia who are holding leadership position. The researchers identify similarities and differences in practices and competencies between two cases. The findings in this study highlights in a set of the practices of which Muslim women leaders performance in leadership position. These findings broaden acceptance for a wider repertoire of these leadership practices by successful Muslim women leaders and how these practices can be optimally used for the benefit of academic departments. Moreover, some implications and recommendations for further studies were discussed.